Hemophilia treatment in 2021: Choosing the"optimal" treatment using an integrative, patient-oriented approach to shared decision-making between patients and clinicians. (March 2022) - Hermans, Cedric; Noone, Declan; Benson, Gary; Dolan, Gerry; Eichler, Hermann; Jiménez-Yuste, Víctor; Königs, Christoph; Lobet, Sébastien; Pollard, Debra; Zupančić-Šalek, Silva; Mancuso, Maria Elisa
Abstract: The mainstay of hemophilia treatment is to prevent bleeding through regular long-term prophylaxis and to control acute breakthrough bleeds. Various treatment options are currently available for prophylaxis, and treatment decision-making is a challenging and multifaceted process of identifying the most appropriate option for each patient. A multidisciplinary expert panel convened to develop a practical, patient-oriented algorithm to facilitate shared treatment decision-making between clinicians and patients. Key variables were identified, and an algorithm proposed based on five variables: bleeding phenotype, musculoskeletal status, treatment adherence, venous access, and lifestyle. A complementary, patient-focused preference tool was also hypothesized, with the aim of exploring individual patients' priorities, preferences, and goals. It is hoped that the proposed algorithm and the hypothesized patient preference tool will assist in selecting a treatment for each patient that is as efficient as possible in preventing bleeds while also accounting for the patient's expectations and priorities.